Development E-LKPD Interactive Based on Socio Scientific Issues (SSI) on Climate Change to Facilitate Student’s Critical Thinking - Novita Aulia Safitri; Asep Saefullah; Rahmat Firman Septiyanto (Universitas Jember, 2025)
This research was conducted agains the background of the low critical thinking of students in Indonesia which can be overcome by the socio scientific issues (SSI) approach by the socio scientific issues (SSI) approach by connecting science with socisl issues such as climate change. With the SSI approach, E-LKPD makes learning more interactive, increases student involvement and overcomes teacher-centered learning. The purpose of this study was to determine the development process of interactive E-LKPD based on socio scientific issues (SSI). The research method used is R&D with 4-D research model modified with the define, design, and development stages. This research has developed an interactive E-LKPD based on socio scientific issues (SSI) on climate change material to facilitate students’ critical thinking in digital form through the help of the liveworksheets website which is categorized as very feasible. The results of material expert validation obtained a percentage of 93.8% which was categorized as very feasible and the results of media expert validation obtained a perentage of 82.2% which was also categorized as very feasible. Student responses to the E-LKPD readability test was 90.8% which was classified as high.